Understanding links between gender and pay: An important role for heterodox economics - Jefferson, Therese; Austen, Siobhan (University of Sydney * Faculty of Economics and Business, 2015)
In early 2013 the prominent mainstream economist, Judith Sloan, claimed that the Workplace Gender Equality Agency (WGEA) was ‘ignorant’ about both economics and statistics (Sloan, 2013). The cause of Sloan’s claim was a WGEA press release about the gap between salaries received by men and women who were recent university graduates. Sloan argued that men and women work in different occupations, with men concentrated in some of the higher earning categories of dentistry and engineering. Her implicit argument was that women’s relatively lower earnings can be explained partly by their ‘choices’ with respect to workforce participation. In a nutshell, according to Sloan, more men than women choose highly paid occupations such as dentistry and engineering and thus their higher earnings are justified. The basic argument, expressed by Sloan, is that valid comparisons of average salaries should take into account all the factors that affect men’s and women’s pay, including their different choices and patterns of workforce participation. In effect, if we are not comparing ‘like with like’, then it may be possible that observed gender-based differences in pay are justified. Sloan’s argument reflects the basis of standard mainstream economic analyses of gender and pay in Australia and internationally. However, increasingly detailed analyses using this approach have shed relatively little light on the causes of women’s relatively low wages.The purpose of this article is to review the extent to which mainstream economic methods have been successful, or otherwise, in explaining a substantial and ongoing gap in the earnings of men and women in Australia which, by commonly used measures described later, had grown to approximately 18 per cent in May 2014, compared with 16.2 per cent in November 2007 (ABS 2008, 2014). It then goes on to argue that insights into the possible causal links between gender and pay can only be achieved by analyses that extend beyond the factors that can be included in mainstream analysis. Thus, if a more complete picture of links between gender and pay is to be achieved in the future, an important role must be played by heterodox economists willing to use alternate analytical approaches. As discussed in this article, heterodox approaches to the analysis of gender-based differences in labour markets typically do not rely on complex statistical procedures but contribute both statistical evidence and detail on the relevant history, industrial organisation and structures of labour markets. Importantly, heterodox economists can also continue to contribute to debates on the gender pay gap by providing critiques of mainstream analyses, with the aim of elucidating the meaning and limitations of different gender pay gap estimates. Both the critiques and analyses undertaken by heterodox economists can play an important role in policy development and reform aimed at improved gender equity in the Australian labour market.